Balanga Technology Center an integrated technology business incubator and data center - Bacila, Ysabelle Coelyn M.
The City of Balanga is known for its student dominated population as different universities and colleges cluster together in a district called "University Town". With a vision to be a "World Class University Town 2020 : an emerging hub for technology-related businesses in the Philippines", the need for Information and Communications Technology (ICT) infrastructures and technological assistance arise. To boost the City's slow economic pace, engaging the community in an entrepreneurial mindset through the use of ICT can create a progressive business economy that can attract public and private organizations to invest in the City the large pool of human resource in the University Town is a big potential for micro, small, and medium enterprises to flourish. This project aims to find architectural solutions on application of ICT in startup business that fosters collaboration and innovation between the government, academic institutions, and private-sectors for economic development and regeneration of the ecosystem of the City of Balanga.